1994
DOI: 10.1002/cne.903430105
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic immunocytochemical analysis of the neurovascular relationships of choline acetyltransferase and vasoactive intestinal polypeptide nerve terminals in the rat cerebral cortex

Abstract: Acetylcholine or vasoactive intestinal peptide (VIP) nerve terminals closely related to intracortical blood vessels have previously been reported. Recent physiological evidence indicates that these central neuronal systems are involved in the fine control of local cerebral blood flow. In the present study, the intimate associations between choline acetyltransferase (ChAT) and VIP axon terminals and intracortical microvessels were characterized by light (LM) and electron microscopic (EM) immunocytochemistry. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 86 publications
4
41
1
Order By: Relevance
“…Some studies reported that the significant part of cholinergic varicosities form conventional synapses with dendritic shafts and spines (Frotscher and Leranth, 1985;Smiley et al, 1997;Turrini et al, 2001), while others described the low incidence of synaptic specializations (Aoki and Kabak, 1992;Chedotal et al, 1994;Umbriaco et al, 1994Umbriaco et al, , 1995Vaucher and Hamel, 1995;Mechawar et al, , 2002. We revisited this issue by investigating the presence or absence of synapse-like specializations, including parallel membrane apposition of cholinergic varicosities and other neuronal elements, uniform cleft width between the apposed membranes, and thickening of the apposed membranes.…”
Section: Cholinergic Varicosities Rarely Make "Classical" Synapsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported that the significant part of cholinergic varicosities form conventional synapses with dendritic shafts and spines (Frotscher and Leranth, 1985;Smiley et al, 1997;Turrini et al, 2001), while others described the low incidence of synaptic specializations (Aoki and Kabak, 1992;Chedotal et al, 1994;Umbriaco et al, 1994Umbriaco et al, , 1995Vaucher and Hamel, 1995;Mechawar et al, , 2002. We revisited this issue by investigating the presence or absence of synapse-like specializations, including parallel membrane apposition of cholinergic varicosities and other neuronal elements, uniform cleft width between the apposed membranes, and thickening of the apposed membranes.…”
Section: Cholinergic Varicosities Rarely Make "Classical" Synapsesmentioning
confidence: 99%
“…Some electron microscopic studies reported that cholinergic varicosities commonly make synaptic contact in the cerebral cortex (66% in rat, Turrini et al, 2001; 67% in human, Smiley et al, 1997), while other studies reported much lower incidence [6 -14% in rat hippocampus and cerebral cortex (Chedotal et al, 1994;Umbriaco et al, 1994Umbriaco et al, , 1995Vaucher and Hamel, 1995;Mechawar et al, 2000Mechawar et al, , 2002 21% in cat visual cortex (Aoki and Kabak, 1992)]. This large difference could be attributable to differences in animal species, cortical regions, and the criteria of synaptic contact.…”
Section: Is Scarce In Cortical Gabaergic Interneuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, VIPcontaining neuronal fibers are intimately associated with the intracortical blood vessels (Eckenstein and Baughman, 1984;Chédotal et al, 1994aChédotal et al, , 1994b. Second, the application of VIP induces a dilatation of pial arteries (Yaksh et al, 1987).…”
Section: Potential Implications Of Nicotinic Receptor-mediated Excitamentioning
confidence: 99%
“…Furthermore, the release of neurotransmitters from monoaminergic and cholinergic subcortical afferents can evoke both a neural and CBF response concurrently. For instance, the release of acetylcholine from afferents originating in the basal forebrain [66,67] alters cortical neuronal activity, but also concurrently evokes increases in CBF [68]. The vascular response appears to be partly mediated by local somatostatin-or neuropeptide Y-positive or GABAergic interneurons [69] and/or astrocytes [67].…”
Section: (D) Central Neuromodulatory Pathwaysmentioning
confidence: 99%